Interlanguage Of Criticism By Indonesian Learners Of English - Ardiyani, Septiana, Agus Wijayanto, Ph.D, Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This research aimes at finding the criticism strategy, hedging strategy, and politeness strategy used by Indonesian learners of English. The data are criticism utterances taken from Indonesian learners of English or English Foreign Language (EFL) students. In collecting the data the writer uses "Pilot Study" with following steps: (1) Grouping the subject, every group consists of four students (2) Asks every subject (EFL) students to draw a picture, the picture is an animal (3) Every subject (EFL) students criticize their friends' work in pair. To analyze criticism utterances, the writer uses Nguyen formula. To describe the using of hedging strategy, the writer uses Martin theory. To describe the politeness system used in criticism utterances, the writer uses Politeness Strategy by Brown and Levinson. Having analyzed the data, the writer found that there are two ways of criticism: direct criticism and indirect criticism. In direct criticism (48%) the writer found six strategies: (1) negative evaluation (15%), (2) disapproval (19%), (3) expression of disagreement (7%), (4) identification of problem (50%), (5) statement of difficulties (6%), (6) consequences (3%). While in indirect criticism (52%) the writer found nine strategies: (1) correction (5%), (2) indicating standard (7%), (3) demand for change (17%), (4) request for change (12%), (5) advice about change (10%), (6) suggestion for change (17%), (7) expression of uncertainty (2%), (8) asking/presupposing (19%), (9) other hints/sarcasm (11%). The writer also found three types of hedging strategy used: (1) strategy of indetermination (54%), (2) strategy of camouflage (5%), (3) strategy of subjectivisation (41%). There are four politeness strategies used: (1) bald on-record strategy (36%), (2) positive politeness strategy (26%), (3) negative politeness (16%), (4) off record (22%).